Marine Tourism Management Strategy On Lanjukang Island: The Role Of Local Government Maritime Diplomacy - Diva Pancarani Arifianti; Seniwati Seniwati (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This article examines the management of marine tourism in Lanjukang Island, a tourist destination located in the Spermonde Islands, Makassar City, South Sulawesi, with a focus on the role of maritime diplomacy in increasing tourism potential while preserving marine resources. This research uses a qualitative approach with literature study methods and interviews with relevant parties, such as local governments and local communities. Lanjukang Island, with its beautiful underwater nature and beaches, faces challenges in the form of coral reef damage due to destructive fishing practices and coastal abrasion processes. Nevertheless, Lanjukang Island remains an attractive tourist destination for domestic and foreign tourists. The Makassar City Government plays an active role in promoting marine tourism through international collaboration, one of which is through the Makassar International Eight Festival and Forum (F8) event. Maritime diplomacy, which emphasizes international cooperation in marine resource management and tourism, plays a key role in facilitating sustainable tourism development on Lanjukang Island. The research found that while there is great potential in the marine tourism sector, more integrated and sustainable management is needed to support the local economy and the preservation of the marine environment. Collaboration between government, community and international partners is essential to achieve a balance between tourism development and nature conservation.